Results of a phase II, open‐label, non‐comparative study of intralesional PV‐10 followed by radiotherapy for the treatment of in‐transit or metastatic melanoma. Issue 7 (23rd February 2017) - Foote, Matthew; Read, Tavis; Thomas, Janine; Wagels, Michael; Burmeister, Bryan; Smithers, B. Mark
Abstract : BACKGROUND: In‐transit and recurrent dermal or subcutaneous melanoma metastases represent a significant burden of advanced disease. Intralesional Rose Bengal can elicit tumor selective ablation and a T‐cell mediated abscopal effect in untreated lesions. A subset of patients in a phase II trial setting received external beam radiotherapy to their recurrent lesions with complete or partial response and no significant acute radiation reaction. METHODS: An open‐label, single‐arm phase II study was performed to assess the efficacy and safety of PV‐10 followed by hypofractionated radiotherapy. Patients had in‐transit melanoma metastases suitable for IL therapy and radiotherapy. RESULTS: Fifteen patients were enrolled and thirteen completed both treatment components. The overall response rate was 86.6% and the clinical benefit was 93.3% on an intention to treat analysis (CR 33.3%, PR 53.3%, SD 6.7%). The median follow up duration was 19.25 months. Size of metastases (<10 mm) predicted lesion complete response (74.6%). Treatment was well tolerated with no associated grade 4 or 5 adverse events. CONCLUSIONS: The combination of PV‐10 and radiotherapy resulted in lesion‐specific, normal tissue‐sparing, ablation of disease with minimal local or systemic adverse effects.